Pemanfaatan Data Biologi Ikan Cakalang (Katsuwonus pelamis) dalam Rangka Pengelolaan Perikanan Bertanggung Jawab di Perairan Teluk Bone - Jamal, Muhammad; Sondita, Muhammad Fedi Alfiadi; Haluan, John; Wiryawan, Budy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
The Bone Bay is part of Fisheries Management Zone WPPI 713 that covers Makassar strait, Flores sea and Bali sea. To such vast marinearea, fisheries management can be started from smaller region, e.g. embayment waters. Biological characteristics of skipjack tuna (Katsuwonuspelamis) are some of important information for developing fisheries management in the area. This research was aimed to determine length-weight relationship, size composititon, growth pattern and biologically feasible size of the fish. Data were obtained from fish caught byfisherman from Januari to December 2007. The bay was divided into three study areas, i.e. Northern, Centre and Southern Zones. The bcoefficients for length-weight relationship in the three zones were equal 3 [not significant]. The average fork-length (FL) in each zoneshowed similar trends: increased from January to June, then stabilized until December. Using von Bertalanffy’s growth model, the maximumFL (L ∞ of 759.75 mm is estimated for fish at age of 84 months. The length at first maturity of the fish is 465 mm (FL).